Green Growth : Lessons from Growth Theory - Withagen, Cees (World Bank, Washington, DC, 2013)
This paper reviews dynamic general equilibrium models in order to collect insights on the interaction between economic growth and environmental issues. The authors discuss the Ramsey model and extend it for natural resource inputs and pollution, as well as for endogenous technical change. Green growth becomes within reach if there is good substitution, a clean backstop technology, a small share of natural resources in gross domestic product, and/or green directed technical change.